2016
DOI: 10.1002/oby.21608
|View full text |Cite
|
Sign up to set email alerts
|

Diet‐induced obese mice exhibit altered immune responses to acute lung injury induced by Escherichia coli

Abstract: ObjectiveObesity has been associated with impaired immunity and increased susceptibility to bacterial infection. It also exerts protective effects against mortality secondary to acute lung injury. The effects of obesity on immune responses to acute lung injury induced by Escherichia coli were investigated to determine if the above‐mentioned differences in its effects were related to infection severity.MethodsDiet‐induced obesity (DIO) and lean control mice received intranasal instillations of 109 or 1010 CFUs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 34 publications
4
35
0
Order By: Relevance
“…The mice receiving high-fat diet exhibited higher body weight, Lee's index, and levels of TC and TG than those receiving normal diet, which indicated that the DIO mouse model was established as previously described by Wan et al [4]. Altunkaynak et al [8] found that high-fat diet induced 6 Journal of Immunology Research 7 Journal of Immunology Research splenomegaly in female SD rats fed with high-fat diet for a 3-month duration.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…The mice receiving high-fat diet exhibited higher body weight, Lee's index, and levels of TC and TG than those receiving normal diet, which indicated that the DIO mouse model was established as previously described by Wan et al [4]. Altunkaynak et al [8] found that high-fat diet induced 6 Journal of Immunology Research 7 Journal of Immunology Research splenomegaly in female SD rats fed with high-fat diet for a 3-month duration.…”
Section: Discussionmentioning
confidence: 68%
“…Obesity is growing rapidly around the world, and the diseases associated with obesity have been highlighted in recent years, especially pulmonary disease. Recently, studies suggested that obesity plays a beneficial role in E. coli pneumonia, manifesting that clinically significant changes in pulmonary inflammatory response may be associated with immune status in obesity [4,5]. The spleen is the center of cellular immunity and humoral immunity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations